Development of a Mixing Process Using an HB-Type Impeller to Easily Achieve Scale-Up by Maintaining Geometrical Similarity - Yoshihito Kato; Haruki Furukawa; Yasuyuki Ikeda; Toshikazu Nakanishi; Tadashi Sano; Kenji Tomioka (International Journal of Chemical Engineering)
In recent years, a novel home base-type (HB-type) impeller was developed to be based on observation of the streak line pattern. An HB impeller must be simple, speedy, and stable (3S). When an HB impeller is used on the laboratory beaker scale, the mixing performance of the HB impeller is better than that of a normal cylindrical stirring bar. In addition, an industrial-scale HB impeller has been constructed based on the observation of the streak line and isolated mixing regions in the vessel. The present authors believe that scale-up of the mixing process is very easy because the geometrical shape of the impeller can be kept consistent when scaling up from the laboratory scale to the industrial scale.